La necropoli neolitica a domus de janas di S. Pietro di Sorres in Comune di Borutta - Sassari (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2009)
The necropolis of Sorres is in the Borutta area in the province of Sassari. It’s located along the southeast side of the hill of Sorres, on which stands the impressive Romanesque church of San Pietro di Sorres (XI-XII sec.), once seat of the medieval diocese. The necropolis is presently composed of five artificial grotticella tombs, a type of domus de janas (house of fairies), dug in the calcareous rock during the Neolithic and used throughout the Aeneolithic. It is assumed that the area was the burial cave of Ulàri, a large karstic cavity whose entrance opens along the north side of the hill; the cave has given back archaeological remains, from the Neolithic period until the Middle Ages. The necropolis of Sorres, although it was restored in the form of hypogeal environments and used for different purposes, is one of the main evidences of the capillary texture of the settlements in Northern Sardinia.
Keywords: Neolitic; necropoli; domus de janas; Sorres; Brutta; Sardinia